Lagi kitang mamahalin a tribute to a national artist - Viva Records Corporation; Toledo, Josefino Musical Director, Arranger and Conductor; Viva Entertainment Co. (Philippines Viva Records Corp., 2003)
In this scene from the Sarzuela Paglipas ng Dilim made famous by National Artist for Theater, Atang de la Rama, the rich and wordly Caridad, played by Rosel Nava tries to distract Ricardo who has fallen in love with the seamistress Estrella
Written in 1919, Dalagang Bukid was the very popular zarzuela that launched the career of Atang de la Rama. Performed over the thousand times, it reflects the social meliue of the era through the story of Angelita, a young girl who is torn between marrying the wealthy Don Silvestre or her childhood sweethear Cipriano.
An excerpt from Walang Sugat a romantic musical set during the Philippine revolt against Spain. In this scene the heroine Julia, originally played by Atang de la Rama, and the women are seemingly engaged in the mundane domestic chore of sewing, but they are singing of weaving their dreams of nationhood with the larger struggle being waged in the country side.
Part 1: Contents: 1.Jubilate, Philippine Philharmonic Orchestra (Lucio San Pedro) Filscap, Video by Horacio Cabangan Jr. & Lino Matalang Jr. 2.Lagi Kitang Naaalala (Leopoldo Silos-Levi Celerio) Filscap, Regine Velasquez. 3.Excerpts from Paglipas ng Dilim Filscap (Leon Ignacio-Precioso Palma). 4.Pipitonggatang ng Kalesahan Medley (Lyrics by Levi Celerio). 5.Kahit Na Magtiis (Ermani Cuenco-Joseph Estrada) BMG Eugene Villaluz. 6.Filipino Love Songs Medley (lyrics by Levi Celerio). 7.Excerpts from Dalagang Bukid (Leon Ignacio-Hermogenies Hagan) Filscap. 8.Bato sa Buhangin (Ernani Cuenco- Snaffa Roger) BMG-BAMI STREAMLINE. 9.Sa Ugoy ng Duyan (Lucio San Pedro-Levi Celerio) Filscap Garry Valenciano with Ballet Philippines. 10.Nahan (Ernani Cuenco-Levi Celerio) BMG Jong Cuenco, Instrumentalist ; Video by Horacio Cabangan Jr. & Lino Matalang Jr. with excerpts from the works of movie directors Gary De Leon, Lamberto Avellana, Lino Brocka, Ishmael Bernal and Eddie Romero
Part 2 Contents: 1.Alamat ng Lahi (Lucio San Pedro) Filscap - a choral opus based on Alamat ng Lahi a poem by Amado Hernandez. National Artist for Literature and the husband of Atang de la Rama. 2.Galawgaw / Alembong (Juan Silos Jr. & Levi Celerio) Filscap-Bituin Escalante & Sheila Francisco, DJ Malock & DJ Noel, atmospheres and beats. 3. Bituing Marikit (Nicanor Abelardo-Servando de los Angeles) P.D. Verni Varga. 4.Waray-Waray (Juan Silos, Jr. - Levi Celerio) Filscap - Jolina Magdangal, Ballet Philippines 5. Araw-araw sa Maynila (Lucio San Pedro, Bien Lumbera) Filscap - Wency Cornejo. 6.Ang Karayom at Iduro (Fulgencio Tolentino-Severino Reyes) P.D. 7. Bayan Ko. (Constancio de Guzman-Jose Corazon de Jesus) Filscap, Jose Llana & Isay Alvarez with Tanghalang Pilipino, Philippine Madrigal Singers, UP Vocal Ensemble, UP Chorus Class. 8. Kahit Konting Pagtingin (Gomez/Hammond-Levi Celerio) Filscap-Sharon Cuneta & Paolo Santos, Guitarist. 9. Lagi Kitang Naaalala (Reprise) Philippine Madrigal Singers & Ensemble
Anong Sarap: Calvin Millado & Roselle Nava with Tanghalang Pilipino
Estrella: Calvin Millado & Lorna Llames with Tanghalang Pilipino
Diligin mo ng Hamog ang Uhaw na Lupa (Ernani Cuenco) BMG - Jason Velasquez & Trex Ordonez
Sapagkat Kami ay Tao Lamang (Tony Marquez) Filscap - Dexter and Anna Fegi.
Keywords: Zarzuela; Songs -- OPM